2015
DOI: 10.1016/j.jphs.2015.02.007
|View full text |Cite
|
Sign up to set email alerts
|

A protective role of Nox1/NADPH oxidase in a mouse model with hypoxia-induced bradycardia

Abstract: Although it has been reported that endotoxin-induced expression of Nox1 in the heart contributes to apoptosis in cardiomyocytes, functional role of Nox1 at the physiological expression level has not been elucidated. The aim of this study was to clarify the role of Nox1 under a hypoxic condition using wild-type (WT, Nox1(+/Y)) and Nox1-deficient (Nox1(-/Y)) mice. ECG recordings from anesthetized mice revealed that Nox1(-/Y) mice were more sensitive to hypoxia, resulting in bradycardia, compared to WT mice. Atri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Although both the loss of sinus rhythm during the clonic phase and the abrupt return of sinus rhythm during mechanical resuscitation closely coincide with respiratory changes, the pO2 and pCO2 are undoubtedly very different at these two points in time. Furthermore, several studies in mice have demonstrated that the initial response to hypoxia, ≤12% O 2 , is a reflex increase in heart rate followed by a decrease with no loss of P-wave over several minutes [1619]. Hypercapnia (5%-6% CO 2 ) decreases heart rate, but does not eliminate SA nodal activity [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Although both the loss of sinus rhythm during the clonic phase and the abrupt return of sinus rhythm during mechanical resuscitation closely coincide with respiratory changes, the pO2 and pCO2 are undoubtedly very different at these two points in time. Furthermore, several studies in mice have demonstrated that the initial response to hypoxia, ≤12% O 2 , is a reflex increase in heart rate followed by a decrease with no loss of P-wave over several minutes [1619]. Hypercapnia (5%-6% CO 2 ) decreases heart rate, but does not eliminate SA nodal activity [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Besides the detrimental CVB3-induced inflammatory effect, also oxidative stress leads to an aggravation of myocardial injury [ 37 ] and thus exacerbates inflammation [ 38 ]. No changes were found in the expression of NOX1 and NOX4, which comprise two of the seven NADPH oxidases members [ 39 ] and are a major source of ROS [ 40 ]. However, iNOS and eNOS, the two main members of the NO family synthases [ 41 ], were differently expressed in CX3CR1 -/- CVB3 mice compared to WT CVB3 animals: whereas eNOS was downregulated in CX3CR1 -/- CVB3 versus WT CVB3 mice, iNOS expression was increased in those mice.…”
Section: Discussionmentioning
confidence: 99%
“…However, NOX‐1 has also been reported to play a protective role against hypoxia‐induced SAN dysfunction. The recent report revealed that NOX‐1‐deficient (Nox1−/Y) mice are more sensitive to hypoxia and bradycardia than the WT mice, suggesting the physiological role of NOX‐1 in cardiac diseases 47 . Moreover, an elevated NOX‐2 expression and p47phox translocation was associated with increased activity of NOX enzymes, which resulted in elevated lipid peroxidation and the activation of ERK and JNK signalling leading to cell death after ischaemia‐reperfusion (I/R) 48 .…”
Section: Human Pathologies and Nox Connectionsmentioning
confidence: 99%